EKSTRAKSI HIJAU SENYAWA BIOAKTIF DARI ALGA MERAH (Eucheuma cottoni) MENGGUNAKAN PELARUT EUTEKTIK DAN APLIKASINYA DALAM SEDIAAN LOSION - Rahmalia, Winda; Adhitiyawarman, Adhitiyawarman; Sayekti, Endah; Prayitno, Dwi Imam (Tanjungpura University, 2026)
The need for environmentally responsible extraction techniques has driven the development of green alternatives to conventional organic solvents. Deep eutectic solvents (DESs) offer a sustainable option due to their low toxicity, biodegradability, and simple preparation. In this study, a DES composed of glycine, glycerol, and water (1:11:15 molar ratio) was used as a green extraction medium to isolate bioactive compounds from the red algae (Eucheuma cottonii), providing an eco-friendly solution for efficient marine bioresource utilization. This final product offers a simplified process, as the resulting extract requires no further separation prior to application. The DES exhibited favourable physicochemical properties, including a pH of 5, density of 1300.14 kg/m³, viscosity of 0.0198 Pa·s, and a freezing point below 263.15 K. Phytochemical screening of the DES-based extract confirmed the presence of phenolic and terpenoid compounds. The extract was directly incorporated into sunscreen lotion formulations at concentrations ranging from 0 to 15% (w/w). All formulations showed good homogeneity, with the highest sun protection factor (SPF) value of 8.37 observed in the lotion containing 15% red algae extract. This research shows the success of extracting natural anti-UV ingredients in an environmentally friendly and efficient manner.